2010
DOI: 10.1021/bm9010084
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the Hemocompatibility of PET Surfaces Using Different Sulphated Polysaccharides as Coating Materials

Abstract: In this study, sulphated polysaccharides were investigated in respect to their blood compatibility properties (hemocompatibility). Pure chitosan was treated with sulphating agents such as SO(3)/pyridine complex and chlorosulfonic acid (HClSO(3)) to obtain 3,6-O-sulfochitosan with low and high concentration of sulfur. These synthetically derived materials and the commercially available sulphated polysaccharides heparin and dextran sulfate, both with high concentrations of sulfur, were coated onto PET foils to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 25 publications
3
45
0
Order By: Relevance
“…The same has been reported for PET-Ch. [4] This finding is in accordance to the fact that PS-NH 2 had also no effect on APTT within the tested concentration range (data not shown). BAEA-C-coated PET foils were not included in the clotting time determination studies because QCM-D studies demonstrated that both 6-deoxy-6-aminocelluloses are equally capable to act as anchor layer for CS adsorption.…”
Section: Preparation and Characterization Of Modified Pet Foilssupporting
confidence: 88%
See 3 more Smart Citations
“…The same has been reported for PET-Ch. [4] This finding is in accordance to the fact that PS-NH 2 had also no effect on APTT within the tested concentration range (data not shown). BAEA-C-coated PET foils were not included in the clotting time determination studies because QCM-D studies demonstrated that both 6-deoxy-6-aminocelluloses are equally capable to act as anchor layer for CS adsorption.…”
Section: Preparation and Characterization Of Modified Pet Foilssupporting
confidence: 88%
“…[4,15] In a previous work, the important measure- ment parameters were optimized toward studying the blood coagulation on polysaccharide-coated PET foils. [16] The samples were incubated with fresh human blood, which resulted in the formation of a blood clot on the surface.…”
Section: Preparation and Characterization Of Modified Pet Foilsmentioning
confidence: 99%
See 2 more Smart Citations
“…24 High and low sulfated chitosan can be obtained by using different sulfur-based reagents, where SO 3 /pyridine gave high sulfated chitosan and low sulfated chitosan can be generated with chlorosulfuric acid. 25 Polyurethanes have been used as blood-contacting biomaterials, including catheters, blood filters, blood tubing, due to their excellent mechanical properties, such as strength and elasticity. 26 Several commercial polyurethanes are marketed including Biomer, Pellethane, Mitrathane, and Tecoflex.…”
Section: Introductionmentioning
confidence: 99%